2020
DOI: 10.1097/inf.0000000000002933
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcome Analysis of 94 Children With Brain Abscess in Beijing: A Single-center Retrospective Study

Abstract: Background: There are limit studies about pediatric brain abscess in China. The aim of this study was to analyze clinical characteristics and outcomes of pediatric brain abscess in recent years in China. Methods: The clinical information of children with brain abscess hospitalized in Beijing Children’s Hospital between January 1, 2007 and December 31, 2016 were retrospectively reviewed. Results: Ninety-four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…In this study, we found that the mortality rate of cerebral abscess patients with a history of CHD is 38.3%. This finding is superior to the prior study in China which the overall mortality was 21.6%, with 50.0% of deaths happening in the 1 st week after diagnosis [10]. Another study in Pakistan also shows that the mortality rate is lower than ours, with only 7.5% of prevalence [11].…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, we found that the mortality rate of cerebral abscess patients with a history of CHD is 38.3%. This finding is superior to the prior study in China which the overall mortality was 21.6%, with 50.0% of deaths happening in the 1 st week after diagnosis [10]. Another study in Pakistan also shows that the mortality rate is lower than ours, with only 7.5% of prevalence [11].…”
Section: Discussioncontrasting
confidence: 99%
“…107,112 The presence of intraventricular rupture is strongly associated with in-hospital mortality; the majority of adult and pediatric patients with ventricular rupture die. 109,126 In-hospital outcomes from brain abscess have improved over the past several decades, likely attributable to better general medical care, more widespread and earlier adoption of neuroimaging, improved microbial diagnostics (in particular, culture of anaerobic bacteria), adoption of minimally invasive neurosurgical procedures, and increased effectiveness of CNS penetrating antimicrobial agents. A 2020 population-based study in Denmark found that the crude 30-day mortality rate decreased almost threefold from the 1980s to the 2010s (from 18% to 7%).…”
Section: Discussionmentioning
confidence: 99%
“…The concurrent presence of systemic illness (eg, pneumonia, sepsis) portends poorer prognosis 107,112 . The presence of intraventricular rupture is strongly associated with in-hospital mortality; the majority of adult and pediatric patients with ventricular rupture die 109,126 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies highlight how the clinical diagnosis of brain abscesses can be challenging, especially in pediatric patients [9][10][11][12]. Symptoms at presentation are nonspecific and may include a combination of headache (for 49-97% of patients), mental status changes (28-91%), fever (32-79%), focal neurologic deficit (20-66%), and/or seizures (13-35%).…”
Section: Diagnosismentioning
confidence: 99%